VIX Futures Term Structure: The Predicting Power and Implementation of Trading Strategies - Vähätaini, Satu (My University, 2017)
According to the efficient market hypothesis the current futures prices are unbiased forecasts of the future underlying spot prices and therefore the futures curve today should indicate the direction and the size of the future spot price changes. This study investigates the efficient market hypothesis on the volatility derivatives market and demonstrates that the front month VIX futures term structure has predicting power over the direction and the size of VIX futures prices changes. The findings suggest that the front month VIX futures term structures movements can be used to construct trading strategies which utilize the term structure position as buying and selling signals for long and short volatility positions. The equations for the predicting power of front month VIX futures explain only 1,4 – 12,5 percent of the subsequent VIX futures price changes depending on the period under examination which also suggest that the trades are highly exposed to equity market fluctuations due to the inverse relationship between VIX Index and the underlying equity market. This also suggests that the term structure movements could be used to time an optimal volatility hedge for an equity portfolio. Different strategies are constructed using different exchange traded products (ETP) which have high correlation with equity market. The VIX futures term structure is in contango most of the time which suggests of taking a short position to the volatility derivatives markets. Indeed, the static trading strategies show that the short trades made on ETPs perform the best during tranquil market periods. In case of dynamic trading strategies, the optimal exposure to long and short positions on volatility are timed based on a threshold representing the current term structure movements. Three out of five dynamic portfolio strategies generate high positive returns. Also, long volatility trades generate positive returns when timed based on the term structure movements.
Keywords: VIX Index; VIX Index Futures; VIX futures term structure; ETP; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|